Prevention of Seroma Formation Following Abdominoplasty: A Systematic Review and Meta-Analysis. (1st February 2017) - Seretis, Konstantinos; Goulis, Dimitrios; Demiri, Efterpi C.; Lykoudis, Efstathios G.
Abstract: Background: With seroma formation being the most common complication of abdominoplasty, multiple surgical strategies have been proposed to lower the seroma rate, yet their effectiveness is unclear. Objectives: The objective of this systematic review and meta-analysis was to comprehensively summarize and quantify the effects of preventive surgical measures for seroma in patients undergoing abdominoplasty. Methods: A predetermined protocol was used. An electronic search in MEDLINE, Scopus, the Cochrane Library, and CENTRAL electronic databases was conducted from inception to June 2016. This search was supplemented by a review of reference lists of potentially eligible studies and a manual search of key journals in the field of plastic surgery. Eligible studies were prospective controlled studies, which investigated prevention of seroma formation and reported on seroma rate. Secondary outcomes were rate of hematoma, wound dehiscence, infection, reoperation and hospital readmission, time to drain removal, total drain output, and length of hospital stay. Results: The meta-analysis included nine studies with 664 abdominoplasty patients. Seroma rate was 7.5% in the prevention group and 19.5% in the control group with the odds ratio (95% confidence interval) being 0.26 (0.10-0.67), P = .006, favoring the prevention group. Similar results were also revealed for infection rate, time to drain removal, and length of hospital stay. Subgroup analysis showed that preservation of Scarpa's fascia, tissue adhesives and, possibly, progressive tension sutures reduce, independently, seroma formation. Conclusions: This meta-analysis provides strong evidence that the use of certain preventive measures during abdominoplasty, compared to conventional procedure, reduces seroma formation. Level of Evidence: 2: